Laterally Actuated Si-to-Si DC MEMS Switch for Power Switching Applications - Abdurrashid Hassan Shuaibu; Almur A. S. Rabih; Yves Blaquière; Frederic Nabki (Micromachines)
Electrothermal actuators are highly advantageous for microelectromechanical systems (MEMS) due to their capability to generate significant force and large displacements. Despite these benefits, their application in reconfigurable conduction line switches is limited, particularly when employing commercial processes. In DC MEMS switches, electrothermal actuators require electrical insulation between the biasing voltage and the transmission line to prevent interference and maintain the integrity of the switch. This work presents a chevron-type electrothermal actuator utilizing a stack of <semantics>SiO2/</semantics> Al thin films on a silicon (Si) structural layer beam to create a DC MEMS switch. The design leverages a thin film Al heater to drive the actuator while the <semantics>SiO2</semantics> layer provides electrical insulation, suppressing crosstalk with the Si layer. The electrical contact resistance of a Si-to-Si interface was evaluated by applying a controlled current and measuring the resultant voltage. A low contact resistance of 150 Ω was achieved when an initial contact gap of 2.52 μm was closed using an actuator with an actuation voltage of 1.2 V and a current of 205 mA, with a switching speed of less than 5 ms. Factors such as the contact force, the temperature, and the residual device layer etching angle significantly impact the Si-to-Si contact resistance and the switch’s longevity. The switch withstands a breakdown voltage up to 350 V at its terminal contacts. Thus, it will be robust to self-actuation caused by unwanted voltage contributions, making it suitable for high-voltage and harsh environment applications.